The Impact of Justice on the Roman Empire Proceedings of the Thirteenth Workshop of the International Network Impact of Empire (Gent, June 21-24, 2017) - Hekster, Olivier; Verboven, Koenraad (Impact of Empire, 2019)
The Impact of Justice on the Roman Empire discusses ways in which notions, practice and the ideology of justice impacted on the Roman Empire through three main themes: the emperor and justice, justice in a dispersed empire and differentiation of justice. Readership: All interested in Roman history and law, and anyone concerned with the relation between law, justice and Empire. For the benefit of non-specialists all ancient sources are translated.